Pemetaan Tingkat Kerawanan Bencana Tsunami di Pesisir Barat Daya Provinsi Banten - Elizabeth Anastasya; I Dewa Nyoman Nurweda Putra; IGB Sila Dharma (Journal of Marine and Aquatic Sciences, 2022)
Indonesia is one of the countries that has a high level of natural disasters in the world because of Indonesia's location and geographical position in the rings of fire. One of the most vulnerable disasters in Indonesia is earthquakes, volcanic eruptions to tsunami waves (Mukhtasor , 2007). Based on data from the BNPB on December 22 2018, there was a tsunami disaster in the southwest coast of Banten to the coast of Lampung caused by the eruption of Mount Anak Krakatau. The purpose of this study are to create tsunami hazard map on the southwest coast of Banten Province by using a Geographic Information System (GIS) and then identify which areas are in a very vulnerable class. This research was conducted in February 2020 until May 2020. The analytical method used was descriptive analysis, map overlay analysis, and qualitative analysis. The stages include the preparation of maps and supporting data using the help of Global Mapper 8.0 software, the determination of influential parameters, analysis of tsunami prone areas based on the parameters that affect, and determination of tsunami prone areas. The process of determining tsunami-prone areas is done through a process of weighting and scoring of influential parameters, then overlapping with the help of ArcGis 10.7 software to get a map of the level of tsunami hazard. The factors in this study that affect tsunami hazard are land height, land protection, distance from the tsunami source, coastline shape, and the presence of barrier islands. The total area classified as very vulnerable is around 19,94 km2 on the southwest coast of Banten Province. This indicates the need for disaster management through crisis management and risk management based on more valid research.